2013
DOI: 10.1002/ddr.21112
|View full text |Cite
|
Sign up to set email alerts
|

Role of Thrombelastography (TEG) in Risk Assessment and Guidance of Antithrombotic Therapy in Patients with Coronary Artery Disease

Abstract: Thrombelastography (TEG) is a viscoelastic assay method used to assess whole blood and plasma coagulation kinetics. Specialized platelet mapping assays have been developed for the TEG platform to quantify the extent of platelet inhibition derived from P2Y12 receptor inhibitors, glycoprotein IIb/IIIa inhibitors, and aspirin. In this review, we describe the current evidence and summarize the data supporting the use of TEG in patients with cardiovascular disease. High thrombin-or adenosine diphosphate (ADP)-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In whole blood, maximal clot strength (MA) measured by TEG is the sum of the additive forces generated by aggregating and contracting platelets incorporated into the growing, initially soluble fibrin network, which is cross-linked and stabilized by FXIIIa [ 13 , 20 ]. In a large cohort study of subjects with coronary artery disease by Lev et al, DM was also independently associated with whole blood (platelet-fibrin) clot strength measured by TEG [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In whole blood, maximal clot strength (MA) measured by TEG is the sum of the additive forces generated by aggregating and contracting platelets incorporated into the growing, initially soluble fibrin network, which is cross-linked and stabilized by FXIIIa [ 13 , 20 ]. In a large cohort study of subjects with coronary artery disease by Lev et al, DM was also independently associated with whole blood (platelet-fibrin) clot strength measured by TEG [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombelastography (TEG) is an established clinical laboratory method for analysis of coagulation and fibrinolysis and allows for quantitative measurement of the dynamic processes of clot formation and clot strength [ 12 , 13 ]. We have previously demonstrated the feasibility of measurement of plasma fibrin clot strength by TEG in platelet-poor plasma and correlation with whole blood fibrin TEG measurements [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Platelet rich plasma (PRP) and platelet poor plasma (PPP) were obtained by differential centrifugation as previously described [12,14,15]. In short, PRP was obtained from citrate blood after centrifugation at 180 g for 5 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Recently Kasahara et al reported that platelet-dependent clot retraction requires factor XIII (FXIII), which covalently associates fibrin polymers with protein located within the platelet plasma membrane at lipid rafts [10]. High clot strength in whole blood assays measured by thrombelastography (TEG) appears to be a risk factor for increased risk of coronary thrombosis after coronary stenting and coronary artery bypass grafting (CABG) [11,12]. Antiplatelet therapy may affect local thrombus generation dynamics and fibrin stabilization by inhibiting FXIIIa activity on the surface of platelets or preventing release of FXIIIa into plasma [13].…”
Section: Introductionmentioning
confidence: 99%
“…It also allows for quantitatively determining whether the body environment has a hypercoagulable state, low coagulation, fibrinolysis, or other symptoms. Based on the scope of TEG parameters, personalized approaches to guide antithrombotic therapies could be determined [23][24][25]. Our TEG results revealed that the level of TEG-R was prominently decreased and levels of TEG-MA, TEG-CI, and TEG-α were significantly increased, indicating that the activation of plasma clotting factors and platelet function might account for the enhanced coagulation in cirrhosis with PVT.…”
mentioning
confidence: 89%